2007
DOI: 10.1007/s00270-006-0260-z
|View full text |Cite
|
Sign up to set email alerts
|

Air Embolism Detected During Computed Tomography Fluoroscopically Guided Transthoracic Needle Biopsy

Abstract: Air embolism is a rare but potentially fatal complication of percutaneous needle biopsy of the lung. We report a case of cerebral air embolism which occurred during computed tomography (CT)-guided needle biopsy. Air entering the aorta is depicted on CT-fluoroscopy images of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…HBOT reduces bubble size and consequently removes occlusive bubbles and reduces endothelial damage (4). A literature review has reinforced the notion that the early application of HBOT is beneficial for patients with a cerebral air embolism (7, 8). However, delayed HBOT is probably also effective to increase the likelihood of survival and neurological recovery as the presence of air bubbles have been demonstrated up to 48 hours after the initial event (9).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…HBOT reduces bubble size and consequently removes occlusive bubbles and reduces endothelial damage (4). A literature review has reinforced the notion that the early application of HBOT is beneficial for patients with a cerebral air embolism (7, 8). However, delayed HBOT is probably also effective to increase the likelihood of survival and neurological recovery as the presence of air bubbles have been demonstrated up to 48 hours after the initial event (9).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, a high level of clinical suspicion is essential to ensure rapid diagnosis. Recently, Hirasawa et al (7) reported that CT-fluoroscopy can visualize air entry during the procedure, and the investigators have suggested the use of CT fluoroscopy as a possible means of early detection.…”
Section: Discussionmentioning
confidence: 99%
“…We summarize both the previously reported 16 symptomatic cases with detailed clinical information of air embolism [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and our three cases in Table 3. Hemiplegia was noted on the right (n = 2) or left (n = 8) side in the 10 cases with neurologic symptoms.…”
Section: Symptoms Of Air Embolismmentioning
confidence: 99%
“…The previously reported incidence of air embolism, with or without clinical symptoms, and needle track implantation was 0.01-0.4% [1-4] and 0.01-0.18% [3-6], respectively. Although there are more than 15 case reports [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in the English-language literature, the authors of these reports did not usually present the incidence of these complications in each institution.Therefore we reviewed the cases of air embolism and needle track implantation in 1,400 percutaneous CT-guided thoracic biopsies that …”
mentioning
confidence: 99%
“…The characteristics of symptomatic air embolism, based on the present and previously reported cases, are summarized in the following section (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In the majority of cases, the clinical symptoms of air embolism occur either during or immediately following needle biopsy.…”
Section: Discussionmentioning
confidence: 99%